Acute Effects of Psilocybin After Escitalopram or Placebo Pretreatment in a Randomized, Double‐Blind, Placebo‐Controlled, Crossover Study in Healthy Subjects - Becker, Anna M.; Holze, Friederike; Grandinetti, Tanja; Klaiber, Aaron; Toedtli, Vanja E.; Kolaczynska, Karolina E.; Duthaler, Urs; Varghese, Nimmy; Eckert, Anne; Grünblatt, Edna; Liechti, Matthias E. (Clinical pharmacology and therapeutics, 2022)
The psychedelic psilocybin is being investigated for the treatment of depression and anxiety. Unclear is whether antidepressant treatments interact with psilocybin. The present study used a double‐blind, placebo‐controlled, crossover design with two experimental test sessions to investigate the response to psilocybin (25 mg) in healthy subjects after pretreatment with escitalopram or placebo. The treatment order was random and counterbalanced. Pretreatment consisted of 10 mg escitalopram daily for 7 days, followed by 20 mg daily for 7 days, including the day of psilocybin administration, or 14 days of placebo pretreatment before psilocybin administration. Psilocybin treatments were separated by at least 16 days. The outcome measures included self‐rating scales that evaluated subjective effects, autonomic effects, adverse effects, plasma brain‐derived neurotrophic factor (BDNF) levels, electrocardiogram QTc time, whole‐blood HTR2A and SCL6A4 gene expression, and pharmacokinetics. Escitalopram pretreatment had no relevant effect on positive mood effects of psilocybin but significantly reduced bad drug effects, anxiety, adverse cardiovascular effects, and other adverse effects of psilocybin compared with placebo pretreatment. Escitalopram did not alter the pharmacokinetics of psilocin. The half‐life of psychoactive free (unconjugated) psilocin was 1.8 hours (range 1.1–2.2 hours), consistent with the short duration of action of psilocybin. Escitalopram did not alter HTR2A or SCL6A4 gene expression before psilocybin administration, QTc intervals, or circulating BDNF levels before or after psilocybin administration. Further studies are needed with a longer antidepressant pretreatment time and patients with psychiatric disorders to further define interactions between antidepressants and psilocybin.